The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/bf01300057
|View full text |Cite
|
Sign up to set email alerts
|

Towards the reconstruction of the Holocene vegetation history of Lower Provence: two new pollen profiles from Marais des Baux

Abstract: Abstract. Two new 14C-dated Holocene pollen profiles from Marais des Baux, Bouches-du-Rh6ne, France, are presented. The record begins in the Younger Dryas, when the vegetation consisted mainly of grasses and mugwort (Artemisia). The Preboreal was marked by a transitory expansion of pine forests and was followed by the establishment of a rich deciduous oak-forest that included hazel (Corylus) and elm (Ulmus). During the Boreal, hazel played a dominant role within the oak-forest. The oak forests, which included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 26 publications
1
12
0
2
Order By: Relevance
“…Moreover, previous pollen investigations in the Apennines (Lowe 1992) and other Mediterranean regions, e.g. Provence, France (Andrieu‐Ponel et al . 2000), indicate that the distribution Abies alba during the early Holocene was much wider than today.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous pollen investigations in the Apennines (Lowe 1992) and other Mediterranean regions, e.g. Provence, France (Andrieu‐Ponel et al . 2000), indicate that the distribution Abies alba during the early Holocene was much wider than today.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in this pollen percentage in the subsequent periods at nearby sites (Ruas 1996;Andrieu-Ponel et al 2000;Arobba et al 2004) could be due to the colder temperatures of the Little Medieval Ice Age. Olive cultivation, which has been documented in Liguria and Provence in the 12th to 13th centuries corresponds to the Medieval optimum and to ameliorated agronomical and selective techniques (Quaini 1973;Durand and Leveau 2004).…”
Section: Cultivated and Useful Taxamentioning
confidence: 95%
“…The closest from Cazan were sampled at 25/30 km from the site on both bank of the Durance river and date back to the end of the 1970's (Triat-Laval, 1978). More recently, two well-dated pollen cores were studied in the Marais des Baux (Andrieu-Ponel et al, 2000), around 30 km west from the site, in an area quite similar, edaphically and botanically speaking. In Triat-Laval's study, the Ericaceae -not identified to the genus level -show a subcontinuous curve (but never exceed 5% of the identified pollen grains) since the end of the Boreal at Beauchamp-Pani eres and Moll eges and appear sporadically at Les Autures but are not recorded at L'Isle-sur-la-Sorgue.…”
Section: Heated-stone Hearthsmentioning
confidence: 99%